(FA0.83MA0.17)0.95Cs0.05Pb(I0.83Br0.17)3 Perovskite Films Prepared by Solvent Volatilization for High‐Efficiency Solar Cells. Issue 11 (8th October 2021) - Zhang, Qiqi; Conkle, Keonna; Ahmad, Zachary; Ray, Paresh Chandra; Kołodziejczyk, Wojciech; Hill, Glake Alton; Gu, Xiaodan; Dai, Qilin
Abstract : Perovskite solar cells (PSCs) have attracted significant research efforts due to their remarkable performance. However, most perovskite films are prepared by the antisolvent method which is not suitable for practical applications. Herein, a (FA0.83 MA0.17 )0.95 Cs0.05 Pb(I0.83 Br0.17 )3 (CsFAMA) perovskite film fabrication technique is developed using solvent volatilization without any antisolvents. The films are formed through recrystallization via the intermediate phase CsMAFAPbI x Cl y Br z during annealing, leading to high‐quality perovskite films. The perovskite growth mechanism is investigated in terms of controlling the amount of formamidinium iodide and methylammonium chloride in the precursor solutions. The oriental growth of the films via the intermediate phase is confirmed by the grazing‐incidence wide‐angle X‐ray scattering measurements. The photovoltaic properties of the perovskite films are investigated. The PSCs based on the films fabricated using the method exhibit a high efficiency of 20.6%. The method developed in this work is based on solvent volatilization, which exhibits significant potential in high reproducibility, facile operation, and large‐scale production. Abstract : High‐quality (FA0.83 MA0.17 )0.95 Cs0.05 Pb(I0 .83 Br0.17 )3 perovskite films are fabricated by solvent volatilization. This method does not need an antisolvent technique and presents significant potential for large‐scale and large‐area device fabrication. A high power conversion efficiency of 20.6% is obtained by the films. A large area perovskite film of 10 × 10 cm 2 can be fabricated by the method.